2020
DOI: 10.3389/fcell.2020.00729
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cell Therapies for Parkinson Disease: Present Challenges and Future Opportunities

Abstract: In Parkinson's disease (PD), there are currently no effective therapies to prevent or slow down disease progression. Cell replacement therapy using human pluripotent stem cell (hPSC)-derived dopamine neurons holds considerable promise. It presents a novel, regenerative strategy, building on the extensive history of fetal tissue grafts and capturing the potential of hPSCs to serve as a scalable and standardized cell source. Progress in establishing protocols for the direct differentiation to midbrain dopamine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 108 publications
(171 reference statements)
1
53
0
Order By: Relevance
“…In many brain regions, Single-cell RNA sequencing (scRNA-seq) has allowed researchers to identify various cell subpopulations, pinpoint gene signatures and novel cell markers (Cuevas-Diaz Duran et al, 2017 ; Ofengeim et al, 2017 ). Cell replacement has been a long-standing and realistic objective for the treatment of PD (Kim et al, 2020 ; Parmar et al, 2020 ). To uncover the previously unknown cellular diversity in a clinically relevant cell replacement PD model, scRNA-seq was used in the experiment by Tiklová et al ( 2020b ).…”
Section: Nurr 1 At a Glancementioning
confidence: 99%
“…In many brain regions, Single-cell RNA sequencing (scRNA-seq) has allowed researchers to identify various cell subpopulations, pinpoint gene signatures and novel cell markers (Cuevas-Diaz Duran et al, 2017 ; Ofengeim et al, 2017 ). Cell replacement has been a long-standing and realistic objective for the treatment of PD (Kim et al, 2020 ; Parmar et al, 2020 ). To uncover the previously unknown cellular diversity in a clinically relevant cell replacement PD model, scRNA-seq was used in the experiment by Tiklová et al ( 2020b ).…”
Section: Nurr 1 At a Glancementioning
confidence: 99%
“…The use of human iPSCs for cell therapy avoids need for long immunosuppressive treatments, risk of graft rejection and ethical concerns related to the use of human embryos. In this regard, it has been recently shown that dopaminergic progenitors derived from clinical-grade human ESC or iPSC lines are safe and effective for cell-based therapy in PD ( Doi et al, 2020 ; Kim et al, 2020 ). Most importantly, human iPSC transplantation into the putamen of a PD patient suggested graft survival as well as improvement of PD symptoms at 18–24 months after surgery ( Schweitzer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in regenerative medicine approaches to treat neurodegenerative diseases, including HD, is enabling long-term assessment of cell fate, functional properties and potential rescue of disease-associated phenotypes (Jia et al, 2020; Kim et al, 2020). Here we evaluated whether hNSCs implanted in the striata of zQ175 mice are viable and integrate into the host tissue at a time point of 8 months after grafting (equating to roughly a third of the captive’s mouse 2-year lifespan).…”
Section: Discussionmentioning
confidence: 99%